Clinical Findings and Outcomes From Subjects With COVID-19 Pneumonia in an Intermediate Respiratory Care Unit. - Laorden, Daniel; Gholamian-Ovejero, Soraya; Terán-Tinedo, José Rafael; Lorente-González, Miguel; Cano-Sanz, Eduardo; Ortega-Fraile, María Ángeles; Martínez-Alejos, Roberto; Hernández-Nuñez, Joaquín; De La Calle-Gil, Isabel; Navarro-Casado, Rosalía; Neria, Fernando; Zevallos-Villegas, Annette; et al. (Respiratory Care, 2023)
BACKGROUND: Many patients with COVID-19 require respiratory support and close monitoring. Intermediate respiratory care units (IRCU) may be valuable to optimally and adequately implement noninvasive respiratory support (NRS) to decrease clinical failure. We aimed at describing intubation and mortality in a novel facility entirely dedicated to COVID-19 and to establish their outcomes. METHODS: This was a retrospective, observational study performed at one hospital in Spain. We included consecutive subjects age > 18 y, admitted to IRCU with COVID-19 pneumonia, and requiring NRS between December 2020-September 2021. Data collected included mode and usage of NRS, laboratory findings, endotracheal intubation, and mortality at day 30. A multivariable Cox model was used to assess risk factors associated with clinical failure and mortality. RESULTS: A total of 1,306 subjects were included; 64.6% were male with mean age of 54.7 y. During the IRCU stay, 345 subjects clinically failed NRS (85.5% intubated; 14.5% died). Cox model showed a higher clinical failure in IRCU upon onset of symptoms and hospitalization was < 10 d (hazard ratio [HR] 1.59 [95% CI 1.24-2.03], P < .001) and PaO2 /FIO2 < 100 mm Hg (HR 1.59 [95% CI 1.27-1.98], P < .001). These variables were not associated with increased 30-d mortality. CONCLUSIONS: The IRCU was a valuable option to manage subjects with COVID-19 requiring NRS, thus reducing ICU overload. Male sex, gas exchange, and blood chemistry at admission were associated with worse prognosis, whereas older age, gas exchange, and blood chemistry were associated with 30-d mortality. These findings may provide a basis for better understanding outcomes and to improve management of noninvasively ventilated patients with COVID-19.